ANTIBACTERIAL ACTIVITY OF BACANG MANGO (Mangifera foetida L.) LEAVES ETHANOL EXTRACT IN GEL FORMULATION AS ANTI-ACNE - Aditya, Aditya; Jannati, Zahra Shaumi Jasmin; Hartianty, Eka Pebi; Tsurayya, Nadya (Jurnal Ilmiah Farmako Bahari, 2024)
Acne was a chronic skin disorder that was most often found in adolescents, so it frequently caused psychological effects that made the acne fighters look for ways to treat it quickly. Although topical antibiotics effectively treat acne, excessive long-term use can cause resistance. This has led to an interest in natural antimicrobials as an alternative treatment for acne. The natural antibacterial activity of the ethanol extract of bacang mango (Mangifera foetida L.) leaves has previously been reported to have antibacterial effects against Propionibacterium acnes, but only in the form of extracts not formulated into pharmaceutical preparations. Therefore, this study aimed to re-test the antibacterial activity of this extract, which has now been formulated into a gel preparation against the same bacteria. The gelling agent used in the gel formulation was Na-CMC with three different concentrations: 3%, 4%, and 5%. The Agar stab technique tests the antibacterial activity for three different extract concentrations. Those were 10%, 15%, and 20% for optimization of inhibitory activity before being formulated. Based on the results of testing the antibacterial activity of the ethanol extract of bacang mango (Mangifera foetida L.) leaves, an extract concentration of 20% had a more potent inhibitory activity than the others so that this concentration was chosen to be formulated into a gel preparation. After the formulation of the extracted gel, Na-CMC with a concentration of 5% produced a better gel base than other formulations. In addition, the three formulations provided the same inhibitory activity of 10 mm, so it can be concluded that the differences in gelling agent concentrations did not affect the antibacterial activity of the extracts in the preparations. However, a 3 mm decrease in inhibition occurred in the extract after it was formulated into a gel preparation. Even so, the extract gel preparation still has antibacterial activity against Propionibacterium acnes with antimicrobial inhibition zone activity, which is in the moderate category.